A sustentabilidade é importante na organização de mega eventos esportivos? - SOUSA, Ana Luiza Ferreira Cruz e (2023)
The term sustainability is recent, therefore it is pertinent to investigate this concept, so that it is possible to delimit what is Environment, Sustainability and Sustainable Development (SD), in this chapter, sustainability will be presented from the perspective of the DS, that is, the tripod that encompasses the economic, the social and the environmental. Because it seems to us that this vision is the one that adds the most value to sport and humanity as a whole. Thus, we will focus on Mega-events that bring together a large number of participants, occur over a long period and with direct implications in the cities and/or countries that host them and in their magnitude, to be considered sustainable, it must prevent environmental degradation, generate distribution of wealth among the different layers and sectors of society affected, including the entrepreneur himself, preventing the impoverishment of future generations and also meeting individual needs.